Deletion of the Capn1 Gene Results in Alterations in Signaling Pathways Related to Alzheimer’s Disease, Protein Quality Control and Synaptic Plasticity in Mouse Brain - Su, Wenyue; Zhou, Qian; Wang, Yubin; Chishti, Athar; Li, Qingshun Q.; Dayal, Sujay; Shiehzadegan, Shayan; Cheng, Ariel; Moore, Clare; Bi, Xiaoning; Baudry, Michel (Frontiers in Genetics, 2020)
Calpains represent a family of calcium-dependent proteases participating in a multitude of functions under physiological or pathological conditions. Calpain-1 is one of the most studied members of the family, is ubiquitously distributed in organs and tissues, and has been shown to be involved in synaptic plasticity and neuroprotection in mammalian brain. Calpain-1 deletion results in a number of phenotypic alterations. While some of these alterations can be explained by the acute functions of calpain-1, the present study was directed at studying alterations in gene expression that could also account for these phenotypic modifications. RNA-Seq analysis identified 354 differentially expressed genes (DEGs) in brain of calpain-1 knock-out mice, as compared to their wild-type strain. Most DEGs were classified in 10 KEGG pathways, with the highest representation in Protein Processing in Endoplasmic Reticulum, MAP kinase and Alzheimer’s disease pathways. The majority of DEGs were down-regulated and validation of a number of these genes indicated a corresponding decreased expression of their encoded proteins. The results indicate that calpain-1 is involved in the regulation of a significant number of genes affecting multiple brain functions. They also indicate that mutations in calpain-1 are likely to be involved in a number of brain disorders.